Examining Copyright Protection for Open Source Software: Legal Implications in Indonesia - Farishi, Salman; Ayu, Cica Kusmira Sagita (Universitas Negeri Gorontalo, 2025)
The development of information technology in Indonesia has increasingly driven the use of Open Source Software (OSS), which enables open collaboration among developers worldwide. However, the implementation of copyright protection for OSS in Indonesia faces challenges, as the basic principle of copyright, which grants exclusive rights to creators, contradicts the spirit of sharing that lies at the core of OSS. This article aims to analyze the challenges faced in implementing copyright for OSS in Indonesia and explore how the adaptation of copyright regulations can support OSS development. This research employs a descriptive qualitative approach with document analysis and interviews as data collection methods. Data sources are derived from relevant legal literature on copyright, OSS licenses, and interviews with software developers and legal experts in Indonesia. The findings indicate that the mismatch between the exclusive nature of copyright principles and the collaborative spirit of OSS is the main challenge in legal regulation. Moreover, limited understanding of OSS licenses among software developers in Indonesia exacerbates the potential for copyright violations. Therefore, this study recommends the need for updates to the Copyright Law to better support the concept of open licensing and to provide better education for developers regarding the legal implications of using OSS. Strengthening the monitoring system is also necessary to ensure that OSS developers in Indonesia can continue to innovate safely while respecting copyright.